ANALISIS DAMPAK PEMBANGUNAN JALAN TOL TRANS SUMATERA (JTTS) RUAS TERBANGGI BESAR – GUNUNG SUGIH TERHADAP USAHA RUMAH MAKAN DAN USAHA MIKRO KECIL MENENGAH (UMKM) - Ahmad Irfan; Feni Rosalia; Tabah Maryanah (P3M STISIPOL Dharma Wacana Metro, 2021)
The JTTS development policy for the Terbanggi Besar-Gunung Sugih section had both positive and negative impacts. This research is aresearch mix method combining quantitative and qualitative. Respondents in the study were 30 restaurant and UMKM business actors selling souvenirs and vehicle repair shops, as well as 10 new business actors who emerged using purposive sampling technique. The results showed that the restaurant and UMKM sellers of souvenirs and vehicle repair shops experienced a significant decrease in income after the existence of JTTS. Meanwhile, the exit toll at Terbanggi Besar has experienced quite rapid growth in new businesses. Based on the statistical test (1) Development JTTS significant effect on the reduction in income the restaurant business and SMEs sellers of souvenirs and vehicle repair shop on the street Central Crossing Sumatra from exit toll roadTerbanggi Besar to exit the toll Mount Sugih withÂ valuet for 8435 is greater than > 2,048 with an influence of 71.8%. (2) Development JTTS significant effect on the growth of new businesses are emerging withtvaluethe for 8222 is greater than> 2.306 with the effect of 89.4%. (3) Alternative policies for reducing the income of souvenirs-selling restaurants and SMEs as well as vehicle repair shops are: (a) The Government promotion by giving directions culinary region before the exit tollMount Sugih and exit motorwayGreat Terbanggi. (b) For the vehicle repair business, an alternative policy can be adopted for the convenience of obtaining people's business credit (KUR) through a number of banks. Meanwhile, an alternative policy for new business growth that has emerged is the use of exit the Terbanggi Besar toll roadto build a special location for selling.